Acute ICH in patients identified as being treated with either warfarin or direct-acting oral anticoagulant agents (DOACs) from a radiology perspective; a cross-sectional observational of 2359 emergency CT head studies. Issue 4 (April 2020) - Salimin, L.; Barber, F.; Limbada, M.; Khalil, O.; Williams, S.
Abstract : AIM: To determine and compare the rates of acute intracranial haemorrhage (ICH) in emergency computed tomography (CT) head studies performed on patients treated with either warfarin or a direct-acting oral anticoagulant agent (DOAC) in a real-world acute setting from a radiology service perspective. METHOD: A retrospective automated search was undertaken via the hospital's radiology information system (RIS) for emergency CT head studies performed over a 2-year period where the clinical details indicated treatment with warfarin or a DOAC. The report of each scan was reviewed for the presence of unequivocal ICH. Duplicate and follow-up scans were excluded. Other parameters (trauma history and time of scan) were also reviewed. RESULTS: Following exclusions, 2, 359 cases were eligible for analysis; 1, 822 patients were treated with warfarin and 537 treated with DOACs. One hundred and nineteen CT heads, of which 104 were treated with warfarin and 15 treated with DOACs, were positive for various types of ICH. The positive rate for ICH was lower in the DOACs group than the warfarin group; 2.7% (number needed to scan: 37) versus 5.7% (number needed to scan: 17.5; p =0.0067). This is also true in a cohort of patients who had traumatic head injury; 2.14% (number needed to scan: 46.7) versus 5.80% (number needed to scan: 17.2; p =0.02). CONCLUSION: The present study has shown a lower rate of ICH in patients treated with DOACs compared to those treated with warfarin in an acute setting. A similar trend is demonstrated in a cohort of patients with a history of traumatic head injury. Highlights: The use of direct oral anticoagulation (DOAC) is gaining popularity over warfarin. The rate of acute intracranial haemorrhage is lower in patients treated with a DOAC compared to warfarinised patients. The intracranial haemorrhage rate of DOACs is also lower in a cohort of patients with traumatic head injury.